Salinity shifts in marine sediment: Importance of number of fluctuation rather than their intensities on bacterial denitrifying community. (May 2018) - Zaghmouri, Imen; Michotey, Valerie D.; Armougom, Fabrice; Guasco, Sophie; Bonin, Patricia C.
Abstract: The sensitivity of denitrifying community to salinity fluctuations was studied in microcosms filled with marine coastal sediments subjected to different salinity disturbances over time (sediment under frequent salinity changes vs sediment with "stable" salinity pattern). Upon short-term salinity shift, denitrification rate and denitrifiers abundance showed high resistance whatever the sediment origin is. Denitrifying community adapted to frequent salinity changes showed high resistance when salinity increases, with a dynamic nosZ relative expression level. Marine sediment denitrifying community, characterized by more stable pattern, was less resistant when salinity decreases. However, after two successive variations of salinity, it shifted toward the characteristic community of fluctuating conditions, with larger proportion of Pseudomonas -nosZ, exhibiting an increase of nosZ relative expression level. The impact of long-term salinity variation upon bacterial community was confirmed at ribosomal level with a higher percentage of Pseudomonas and lower proportion of nosZII clade genera. Highlights: Denitrification rates were resistant to salinity fluctuation in microcosms. Marine community resist to a single shift of salinity even of strong range. Denitrifying community structure was impacted by the number of salinity fluctuations. Pseudomonas denitrifiers outcompete other member in saline fluctuating conditions.